2010
DOI: 10.3354/ab00268
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in bivalve shells from the Río Cruces, Chile

Abstract: In May 1960, the largest recorded earthquake in the earth's history struck southern Chile, and lowered the course of the Río Cruces by approximately 2 m. This created a wetland, which was colonised by the waterweed Egeria densa and, subsequently, by large populations of the blacknecked swan, which fed on the weed. Reported catastrophic declines in the weed and swan populations in 2004 coincided with the opening of a large cellulose plant upstream, leading to popular and scientific condemnation of the plant. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
2
3
0
Order By: Relevance
“…δ 13 C shell and Sr/Ca ratio are also correlated (P = 0.0154, R = 0.83) only if data from layers 5 and 7 are excluded. These correlations are consistent with the results reported by Risk et al (2010), who have found similar peaks of δ 18 O and Sr/Ca and Ba/Ca ratios in the same species in Chile in summer growth lines, considering that summer is the dry season in both Chilean an Argentine Patagonia. In our study, the Mn/Ca ratio was not considered for the analysis because it does not show any significant trend along the sequence and is not correlated with the other proxies.…”
Section: Stratigraphic Analysessupporting
confidence: 93%
See 1 more Smart Citation
“…δ 13 C shell and Sr/Ca ratio are also correlated (P = 0.0154, R = 0.83) only if data from layers 5 and 7 are excluded. These correlations are consistent with the results reported by Risk et al (2010), who have found similar peaks of δ 18 O and Sr/Ca and Ba/Ca ratios in the same species in Chile in summer growth lines, considering that summer is the dry season in both Chilean an Argentine Patagonia. In our study, the Mn/Ca ratio was not considered for the analysis because it does not show any significant trend along the sequence and is not correlated with the other proxies.…”
Section: Stratigraphic Analysessupporting
confidence: 93%
“…High Mn/Ca ratio has been reported as an indication of high aquatic primary productivity Carroll and Romanek 2008). Particularly for D. chilensis, which shows maximum growth rate in winter (Soldati et al 2009;Rocchetta et al 2014), Risk et al (2010) have detected Mn peaks in winter growth lines interpreting that increased precipitations and river discharge can augment erosion, liberating soluble Mn. According to Lee and Wilson (1969), Sr/Ca ratio is expected to show positive correlation with reduced river discharge and/or with increased evaporation.…”
Section: Interpretation Of the Palaeoenvironmental Datamentioning
confidence: 99%
“…While the low water manganese concentrations (0.1-0.6 ppb) are consistent with Keeney-Kennicutt and Presley's (1986) measurements (0.1-2.3 ppb), we will not draw conclusions based on the water Mn data because our water samples were not filtered and acidified immediately upon collection. Turekian and Scott (1967) attribute the suspended particulate manganese concentration in the Brazos River (690 ppm) to soil erosion, as found in other river Mn studies (e.g., Shiller, 2002;Risk et al, 2010). The highest water Mn concentration values in our study were from samples taken during times of high flow.…”
Section: Water Chemistrysupporting
confidence: 83%
“…The role of river bed sediments and river suspended matter should also be kept in mind. For example, a close correlation in the Mn content of bivalve shells and river discharge was reported to originate from the erosion and downstream transport of Mn-bearing sediments (Risk et al, 2010). In the river water systems of this study, however, the effect of a Mn-rich silicate riverine suspended matrix should be limited because the centered PCA patterns of the data set identify Mn as an important component for both biochemical and geographical factors ( Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 94%